PELEMBAGAAN REFORMASI BIROKRASI DALAM KONTEKS PELAKSANAAN UU APARATUR SIPIL NEGARA DI KABUPATEN SLEMAN - Yanuardi Yanuardi; Utami Dewi; Marita Ahdiyana (Yogyakarta State University, 2016)
This research aims to reveal the institutionalization of bureaucratic reformation in Sleman Regency after the implementation of UU ASN. Moreover, the objective of this study is to identify the potential and inhibited factors of bureaucratic reformation in Sleman Regency. The research method of this research is descriptive by employing qualitative approach. The result of this research show that the institutionalization of bureaucratic reform after the implementation of the Act ASN in Sleman have run, and continued with a change agenda. This is evidenced by the habituation process that has been seen from the implementation of the rules and a new culture in Sleman District Government. The main obstacle was the culture of the old bureaucracy, which asked to be served, causing bureaucratic reform objectives have not been achieved optimally. In addition, the Government of Sleman regency, like other local governments in Indonesia, had to wait for the policy directives from the central government due to frequent policy changes at the central level.Keywords: Institutionalization, Bureaucratic Reformation, UU ASN